Knowledge about air pollution and its protective practice among geriatric population of Kalanki. - Thapa,Salina (2017)
ABSTRACT: Background: Air pollution is one of the present day health problems throughout the world. Exposure to air pollutants can affect human health in various ways, leading to increased mortality and morbidity. The pollution of the Kathmandu Valley's pollution exceeds both the WHO limits multiple. Geriatric populations are more prone to suffer from various complications due to compressed immune system. Methods: A cross-sectional descriptive study using a modified standard questionnaire was conducted among 218 geriatric population of kalanki-14 Kathmandu Nepal. Data was objectively analyzed in SPSS full version 21. Chi-square test. Results: Overall the majority of the respondent was male of 65.1 % and remaining 34.9% were female the mean age of the survey population was 68 8.1. 94% of the population was Hindu. Majority of the survey population i.e. 30.3% of population were illiterate and 27.18% had informal education.99.4% of the total 179 respondent thinks automobile as main source of air pollution and with 95% thinks construction as second main cause of air pollution. Among 179 respondent 94.4% thinks air pollution leads to cough and 88.21% thinks it causes asthama.73.7% of the population learned about air pollution by them. There was association between awareness level and education status with p value (<0.15).Out of 172 surveyed population 57% of population had hypertension. Among total 218 respondent 64.7% of people had below average knowledge level but 88.1% of them had above average level of preventive practice. There was no association between level of knowledge and level of preventive practice. People with below average education level had more problem of respiratory disease. Conclusion: This study reports that the level of knowledge and awareness of air pollution among the geriatric population was below average despite of that the preventive practice of the geriatric population from air pollution was found to be above average and people with below average education level had more frequency of respiratory disease. Key words: Air pollution; geriatric population; Kalanki-14 Kathmandu Nepal